PBL (Problem Based Learning) Model Based on Constructivist Sosioculturalism: Theory and Concept of The Millennial Era of Learning Model - Ilfiana Firzaq Arifin; Akhmad Arif Musaddad; Sudiyanto Sudiyanto (Yupa: Historical Studies Journal, 2018)
Indonesia as a developing country that aspires to improve the quality of education by delivery of human beings who have intelligence that is balanced with high emotional intelligence. Innovation of the learning model is the first step to move forward in advancing the quality of education in this country. The purpose of writing this article is to provide an overview of PBL based learning model constructivist sosioculturalism as an innovative learning model in the millennial era. The method used in this article is descriptive and theoretical analysis with data collected through the study of a variety of articles, books, journals and sources that support the learning model PBL (Problem Based Learning) and constructivist theory sosioculturalism.